SiAlON ceramic and preparation method and application thereof

By adopting Y-REII-REIII ternary rare earth doping technology, the precipitation of α-SiAlON and β-SiAlON of SiAlON ceramics is controlled, which solves the problems of insufficient sintering power and pore residue, and achieves SiAlON ceramics with high mechanical properties, low porosity and high production efficiency.

CN119638445APending Publication Date: 2025-03-18ZHUZHOU HARD ALLOY GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411924241.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing SiAlON ceramics lack sintering power in the late sintering stage, resulting in pore residues, and the single rare earth cation doping has limited ability to regulate the α/β ratio and mechanical properties.

Method used

The precipitation and sintering force of α-SiAlON and β-SiAlON are controlled by the different cation radii of rare earth elements REII and REIII, reducing porosity and improving mechanical properties.

Benefits of technology

SiAlON ceramics with excellent mechanical properties, good heat resistance and low porosity are achieved, and the preparation difficulty is low and the production efficiency is high. They can achieve a relative density of more than 99% by conventional air pressure sintering methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638445A_ABST
    Figure CN119638445A_ABST
Patent Text Reader

Abstract

The invention discloses SiAlON ceramic as well as a preparation method and application thereof. The crystalline phase structure of the SiAlON ceramic comprises an alpha-SiAlON phase and a beta-SiAlON phase, the SiAlON ceramic also comprises three rare earth elements: Y, REII and REIII; the cation radius of REII is less than 0.89; the cation radius of REIII is greater than 1.0. The SiAlON ceramic can be used for manufacturing heat-resistant metal high-speed machining cutters, wear-resistant components or high-temperature refractory materials, has more excellent heat resistance, better comprehensive mechanical properties and lower porosity, is high in production efficiency and low in production cost, and products with different properties can be obtained by adjusting the proportion of raw materials and machining parameters, so that the SiAlON ceramic is suitable for industrial production. The production flexibility is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic materials, and in particular to a SiAlON ceramic and a preparation method and application thereof. Background Art

[0002] In recent years, non-oxide ceramics have been widely used in key fields such as cutting tools, wear-resistant parts, and high-temperature structural materials for extreme service environments due to their excellent high-temperature mechanical properties and chemical stability. Among them, SiAlON ceramics are a new type of non-oxide structural ceramics. On the basis of Si3N4, Si and N atoms are replaced by Al and O atoms to form a new type of solid solution ceramic material based on Si-Al-ON, which has excellent high-temperature hardness, chemical stability and thermal shock resistance. Compared with other non-oxide ceramics, SiAlON ceramics have more outstanding fracture toughness and collapse resistance; compared with Si3N4, the instantaneous liquid phase formed by SiAlON ceramics during the sintering process can be used as a chemical composition to form the SiAlON phase in the later stage of sintering, so that the grain boundaries are purified, so it has better high-temperature mechanical properties and chemical stability. Therefore, SiAlON ceramics are widely used in applications such as heat-resistant metal high-speed machining tools, wear-resistant components and high-temperature refractory materials.

[0003] SiAlON ceramics can be controlled by composition and process parameters to generate two common crystal phases, α-SiAlON and β-SiAlON, and the two can coexist thermodynamically. α-SiAlON has an equiaxed morphology, high hardness and wear resistance, and can consume some rare earth or alkaline earth metal oxides in the grain boundary during the formation process; β-SiAlON mainly exhibits a long rod-like structure, and has excellent toughness and fracture resistance through the grain self-locking effect. α-β-SiAlON is a composite ceramic composed of α-SiAlON and β-SiAlON. It overcomes the shortcomings of poor wear resistance and easy fracture of pure β-phase and α-phase SiAlON ceramics, and is a composite ceramic material with superior comprehensive performance. Therefore, α-β-SiAlON ceramics have attracted much attention as a material for heat-resistant metal cutting tools and wear-resistant parts. At present, many α-β-SiAlON ceramics are doped with a single rare earth cation (e.g., Chinese patent document CN1246254C discloses a method for preparing α-β-SiAlON ceramics by doping with Yb2O3), but the ability of single doping to regulate the α / β ratio and mechanical properties is limited. In addition, in the late stage of sintering, a large number of rare earth cations enter the α-SiAlON lattice, and the liquid phase content between the grains is significantly reduced, resulting in insufficient sintering power and residual pores. Summary of the invention

[0004] The present invention provides a SiAlON ceramic with excellent mechanical properties, good heat resistance, low porosity, low preparation difficulty and high production efficiency, and a preparation method and application thereof, in order to solve the technical problems mentioned in the background technology.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is: A SiAlON ceramic, wherein the crystal phase structure of the SiAlON ceramic includes an α-SiAlON phase and a β-SiAlON phase; the SiAlON ceramic also includes three rare earth elements: Y, RE II and RE III ; The rare earth element RE II The cation radius is less than 0.89Å; the rare earth element RE III The cation radius is larger than 1.0 Å.

[0006] The design idea of ​​the above technical solution is that the present invention adopts Y-RE II -RE III Ternary rare earth doped SiAlON ceramics, in which the rare earth element RE II The cation radius is less than 0.89Å. Such rare earth cations can easily enter the lattice of α-SiAlON to form a coordination structure, which is thermodynamically beneficial to the precipitation of α-SiAlON and meets the wear resistance requirements of SiAlON ceramic tools or structural materials. III The cation radius of the rare earth cation is greater than 1.0 Å. Due to its large size, it is difficult for such rare earth cations to enter the lattice of α-SiAlON and it can only exist in the intercrystalline glass phase. Therefore, it can continuously produce a liquid phase during the sintering process, preventing the problem of insufficient sintering power in the later stage of sintering, and reducing the porosity of the final product. In order to ensure the growth of SiAlON grains, especially β-SiAlON grains with a large aspect ratio, Y2O3 (ionic radius 0.9 Å) is also added in the present invention. Y 3+ There is a good adsorption effect on the (100) surface of SiAlON grains, and most of the Y2O3 will enter the α-SiAlON lattice in the later stage of sintering, which will not significantly deteriorate the grain boundary strength. Therefore, compared with the existing technology, the ternary rare earth doped SiAlON ceramics have better comprehensive mechanical properties.

[0007] As a further preferred embodiment of the above technical solution, the rare earth element RE II At least one of Lu, Yb, Tm and Er is included. Yb is preferred from the perspectives of cost and availability.

[0008] As a further preferred embodiment of the above technical solution, the rare earth element RE III Includes at least one of Ce and La. La is preferred from the perspective of cost and availability.III Cations are easily attached to the (100) surface of SiAlON grains, which is more conducive to the growth trend of SiAlON grains with a large aspect ratio, and can improve the anti-breakage performance of SiAlON ceramics under extreme service conditions.

[0009] As a further preferred embodiment of the above technical solution, in the SiAlON ceramic, the proportion of α-SiAlON phase is 25%~70%, and the proportion of β-SiAlON phase is 30~75%. Among them, when the proportion of α-SiAlON phase is 25~40%, it is suitable for making heat-resistant metal cutting tools for intermittent cutting; when the proportion of α-SiAlON phase is 40~70%, it is suitable for making wear-resistant parts or heat-resistant metal cutting tools for continuous cutting. When the proportion of α-SiAlON phase is lower than 25%, the wear resistance and thermal shock resistance of the sintered body are poor, and there may be more intergranular phase residues; when the proportion of α~SiAlON phase is greater than 70%, the sintered body has poor collapse resistance. The adjustment of the α / β phase ratio mainly depends on the temperature, the content of rare earth oxides or cations, and the type of rare earth cations. Generally speaking, the higher the temperature, the higher the proportion of α phase; the higher the content of rare earth cations within a certain range, the higher the proportion of α phase; the smaller the size of rare earth cations, the higher the proportion of α phase.

[0010] Based on the same technical concept, the present invention also provides a method for preparing SiAlON ceramics of the above technical solution, comprising the following steps: (1) Combine Si3N4, AlN, Al2O3, Y2O3, RE II2 O3 and RE III2 The O3 raw material powder and the binder are dispersed in a solvent according to a proportion and mixed evenly to obtain a mixed slurry; (2) drying the mixed slurry and then performing molding to obtain a ceramic green body; (3) The ceramic green body is sintered under pressure at 1700-1900° C., and then cooled after sintering to obtain the SiAlON ceramic.

[0011] Compared with single rare earth oxide doping, the multi-component rare earth oxide doping used in the present invention can reduce the melting point of the instantaneous liquid phase, which is beneficial to the liquid phase sintering process, thereby reducing the difficulty of sintering SiAlON ceramics. Therefore, a relative density of more than 99% can be achieved by conventional gas pressure sintering methods, and its production efficiency and cost are better than traditional hot pressing or hot isostatic pressing sintering technology; the final sintering temperature is designed to be 1700~1900℃. If the temperature is too low, SiAlON ceramics cannot obtain a good densification efficiency, and if the temperature is too high, Si3N4 will decompose violently, affecting the surface quality and composition control. At the same time, the preparation method of the present invention can also be adjusted by adjusting Y2O3 / RE II2 O3 / RE III2The proportion of O3 and processing parameters can be used to adjust the α / β phase ratio of SiAlON ceramics, so that the mechanical properties can be designed and adjusted for different usage scenarios.

[0012] As a further preferred embodiment of the above technical solution, in step (3), the ceramic green body is first heated to 1500°C at a rate of 10°C / min under vacuum conditions, and then heated to 1700~1900°C at a rate of 5~8°C / min in a 0.1MPa nitrogen atmosphere, and pressure sintered in a 1~10MPa nitrogen atmosphere. The main purpose of vacuum heating to 1500°C is to save gas costs. Silicon nitride will not decompose below 1500°C, and no nitrogen atmosphere or other atmosphere protection is required. In the process of heating to 1700~1900°C, silicon nitride may decompose in an atmosphere lacking nitrogen, so 0.1 MPa nitrogen protection is required. After reaching the sintering temperature, the gas pressure needs to be increased to 1~10 MPa in the later stage of sintering to eliminate closed pores and achieve an ideal density. Generally speaking, silicon nitride-based or SiAlON-based ceramics are sintered at low pressure throughout the process, which may not achieve a relatively ideal density for tool materials. Some methods that use high-pressure sintering (1-10 MPa) use 1~10 MPa for sintering throughout the process after reaching the sintering temperature. The disadvantage of this method is that in the early stage after reaching the sintering temperature, the densification process is mainly to eliminate through holes, but high pressure is not conducive to the elimination of through holes. Secondly, the gas consumption of high-pressure sintering throughout the process is large, which increases the cost. Therefore, this scheme adjusts the sintering atmosphere according to the temperature and sintering state, which can effectively reduce the sintering gas cost and effectively eliminate porosity.

[0013] As a further preferred embodiment of the above technical solution, after the ceramic green body is heated to 1700~1900℃, two-step pressure sintering is performed: first, it is kept warm in a nitrogen atmosphere of 1 MPa for 1 hour, and then kept warm in a nitrogen atmosphere of 6~10 MPa for 1~1.5 hours. A two-step pressurization method is adopted at the sintering temperature. First, the pressure is maintained at 1 MPa N2 for 1 hour. During this process, the SiAlON ceramic uses liquid phase sintering to effectively reduce through holes, and uses N2 protection to inhibit excessive volatilization of Si3N4; then, 6~10MPaN2 pressure is applied to maintain pressure for 1~1.5 hours, and high pressure is used to eliminate closed pores in the sintered body. Compared with the one-step pressurization method, the present invention reduces the gas cost generated by high-pressure sintering throughout the process on the basis of achieving the preparation of high-density SiAlON ceramics.

[0014] As a further preferred embodiment of the above technical solution, Si3N4 powder accounts for 75-90wt% of the total mass of the raw material powder; AlN powder accounts for 2-8wt% of the total mass of the raw material powder; Al2O3 powder accounts for 1-5wt% of the total mass of the raw material powder; Y2O3 powder accounts for 0-10wt% of the total mass of the raw material powder; RE II2O3 powder accounts for 1~11wt% of the total mass of raw material powder; RE III2 O3 powder accounts for 0.1~2wt% of the total mass of raw material powder; among them, Y2O3+ RE II2 O3+RE III2 The total mass of O3 powder accounts for 5-12wt% of the total mass of raw material powder. If it is lower than 5%, good densification effect cannot be achieved. If it is higher than 12 wt%, excessive intercrystalline glass phase will easily remain, and even glass phase segregation problems will occur.

[0015] As a further preferred embodiment of the above technical solution, in step (1), the solvent is anhydrous ethanol, the raw material powder is added to a polytetrafluoroethylene ball mill containing anhydrous ethanol and Si3N4 grinding balls, and the raw material powder and the binder are evenly mixed by planetary ball milling or drum ball milling. The ratio of raw material powder: Si3N4 balls: anhydrous ethanol is 1: (1.5~2.5): (2.5~3.5); if a planetary ball mill is used, the ball milling parameters are a rotation speed of 200~350 rpm and a ball milling time of 4~8 hours; if a drum ball mill is used, the ball milling parameters are a rotation speed of 40~60 rpm and a ball milling time of 24~48 hours.

[0016] As a further preferred embodiment of the above technical solution, in step (2), the mixed slurry is vacuum dried and then passed through an 80-mesh sieve, the obtained mixed powder is loaded into a mold and uniaxially pressed, and then cold isostatically pressed to obtain a ceramic green body with a density of 50-60%; the pressure of the cold isostatic pressing process is 180-300 MPa.

[0017] As a further preferred embodiment of the above technical solution, in step (3), the ceramic green body is dewaxed and then pressure sintered; the dewaxing temperature is 370-800° C., and the dewaxing time is 3-4 hours.

[0018] As a further preferred embodiment of the above technical solution, the binder includes at least one of polyvinyl butyral and microcrystalline wax; the added amount of the binder is 1-6% of the total mass of the raw material powder, and more preferably 3-6%.

[0019] Based on the same technical concept, the present invention also provides an application of the SiAlON ceramic of the above technical solution, wherein the SiAlON ceramic is used to make heat-resistant metal high-speed machining tools, wear-resistant components or high-temperature refractory materials.

[0020] The present invention has the following beneficial effects: (1) The SiAlON ceramic of the present invention is doped with three rare earth elements. Compared with the multi-oxide doping containing alkaline earth metal oxides (such as CaO, MgO, SrO, etc.) commonly used in the prior art, the grain boundary phase of the SiAlON ceramic of the present invention contains only rare earth cations and does not contain alkaline earth metal cations, and has a higher glass transition temperature and Young's modulus, and has better heat resistance. Compared with the single rare earth element doping commonly used in the prior art, the SiAlON ceramic of the present invention has better comprehensive mechanical properties and lower porosity, a hardness HV10 greater than 1700, and a fracture toughness K 1C Greater than 7.5 MPa / m 2 .

[0021] (2) The preparation method of SiAlON ceramics of the present invention can achieve a relative density of more than 99% through a conventional gas pressure sintering method, with high production efficiency and low production cost. Products with different properties can be obtained by adjusting the proportion of raw materials and processing parameters, with high production flexibility.

[0022] The present invention will be further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is the microscopic morphology of the α-β-SiAlON ceramic of Example 1; Figure 2 is the energy dispersive X-ray spectrum of the α-β-SiAlON ceramic of Example 1; Figure 3 is the X-ray diffraction pattern of the α-β-SiAlON ceramic of Example 1 in the range of 29.5°-38.5°; Figure 4 This is the microscopic morphology of the α-β-SiAlON ceramic of Example 2; Figure 5 is the X-ray diffraction pattern of the α-β-SiAlON ceramic of Example 2 in the range of 29.5°-38.5°; Figure 6 This is a microscopic morphology of the α-β-SiAlON ceramic of Example 4; Figure 7 is the X-ray diffraction pattern of the α-β-SiAlON ceramic of Example 4 in the range of 29.5°-38.5°; Figure 8 This is the microscopic morphology of the α-β-SiAlON ceramic of Comparative Example 1; Fig. 9This is the microscopic morphology of the α-β-SiAlON ceramic of Comparative Example 4. DETAILED DESCRIPTION

[0024] The following is a detailed description of the embodiments of the present invention in conjunction with the accompanying drawings, but the present invention can be implemented in a variety of different ways as defined and covered by the claims. Some of the physical and chemical properties of the raw materials used in the embodiments are as follows: Si3N4 (α phase%>95%, D50 = 0.7 μm, oxygen content 1.3 wt%), AlN (D50 = 1.5 μm, oxygen content 1.1 wt%), Al2O3 (D50 = 0.2 μm, purity>99.99%), Y2O3 (D50 = 0.8 μm, purity>99.95%), Yb2O3 (D50 = 1.0 μm, purity>99.9%), Er2O3 (D50 = 1.2 μm, purity>99.9%) and La2O3 (D50 = 1.2 μm, purity>99.9%).

[0025] Embodiment 1: The SiAlON ceramic of this embodiment can be used to make wear-resistant parts or heat-resistant metal cutting tools for continuous cutting. Its crystal phase structure includes α-SiAlON phase and β-SiAlON phase. The proportion of α-SiAlON phase is about 62%, and the proportion of β-SiAlON phase is about 38%. The SiAlON ceramic also includes three rare earth elements: Y, Yb and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.1% of the theoretical density, a hardness of HV10 of 1850, and a fracture toughness of K 1C 7.5 MPa / m 2 The microscopic morphology of SiAlON ceramics (SEM image) is as follows: Figure 1 As shown, the light gray crystals are α-SiAlON, the dark gray crystals are β-SiAlON, and the bright white part is the intercrystalline glass phase. Figure 1 It can be seen that the glass phase ratio is low and evenly distributed. Energy dispersive X-ray spectroscopy (EDS) analysis of this area is as follows Figure 2 As shown in Figure 1, the presence of Y, Yb and La elements can be detected in the energy spectrum. The X-ray diffraction spectrum of SiAlON ceramics in the range of 29.5°-38.5° is shown in Figure 1. Figure 3 As shown by Figure 3 It can be seen that both α-SiAlON and β-SiAlON are precipitated.

[0026] The preparation method of the SiAlON ceramic of this embodiment comprises the following steps: (1) Combine Si3N4, Al2O3, AlN, Y2O 3、Yb2O3 and La2O3 were prepared in a mixed powder at a mass ratio of 82.5%, 3%, 6%, 1.8%, 6.2% and 0.5%. Grinding balls and solvents were prepared in a ratio of mixed powder: Si3N4 balls: anhydrous ethanol = 1:2:3, and 4% of the weight of the powder was added to the slurry as a binder. The mixture was ball-milled at a speed of 250 rpm in a planetary ball mill for 8 hours to obtain a mixed slurry.

[0027] (2) The mixed slurry is vacuum dried and passed through an 80-mesh screen to obtain a mixed powder. The mixed powder is then placed in a mold for uniaxial pressing and then subjected to cold isostatic pressing at 200 MPa to obtain a ceramic green body.

[0028] (3) After the ceramic green body is placed in a resistance furnace to remove the binder (800°C, 3h), it is transferred to a pressure sintering furnace. First, the temperature is raised to 1500°C at a rate of 10°C / min under vacuum, and then the temperature is raised to 1850°C at a rate of 8°C / min under 0.1 MPa nitrogen protection. At this sintering temperature, 1 MPa N2 is applied to maintain the pressure for 1 hour, and then 8 MPa N2 is applied to maintain the pressure for 1 hour, and then the SiAlON ceramic is obtained by cooling in the furnace.

[0029] Embodiment 2: The SiAlON ceramic of this embodiment can be used to make wear-resistant parts or heat-resistant metal cutting tools for continuous cutting. Its crystal phase structure includes α-SiAlON phase and β-SiAlON phase. The proportion of α-SiAlON phase is about 56%, and the proportion of β-SiAlON phase is about 44%. The SiAlON ceramic also includes three rare earth elements: Y, Yb and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.3% of the theoretical density, a hardness of HV10 of 1840, and a fracture toughness of K 1C 8.1 MPa / m 2 The microscopic morphology of SiAlON ceramics (SEM image) is as follows: Figure 4 As shown by Figure 4 It can be seen that the proportion of intercrystalline glass phase is low and evenly distributed, and some β phase grains have a tendency to grow with a large aspect ratio. The X-ray diffraction spectrum of SiAlON ceramics in the range of 29.5°-38.5° is as follows Figure 5 shown.

[0030] The preparation method of SiAlON ceramics in this embodiment is basically the same as that in embodiment 1, except that in step (1) of this embodiment, Si3N4, Al2O3, AlN, Y2O 3、 The mixed powder of Yb2O3 and La2O3 is prepared in the mass ratio of 82%, 3%, 6%, 1.7%, 6.1% and 1.2%.

[0031] Embodiment 3: The SiAlON ceramic of this embodiment can be used to make wear-resistant parts or heat-resistant metal cutting tools for continuous cutting. Its crystal phase structure includes α-SiAlON phase and β-SiAlON phase, with the proportion of α-SiAlON phase being about 62% and the proportion of β-SiAlON phase being about 38%. The SiAlON ceramic also includes three rare earth elements: Y, Yb and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.4% of the theoretical density, a hardness of HV10 of 1840, and a fracture toughness of K 1C 7.8 MPa / m 2 .

[0032] The preparation method of SiAlON ceramics in this embodiment is basically the same as that in embodiment 1, except that in step (1) of this embodiment, Si3N4, Al2O3, AlN, Y2O 3、 The mixed powder of Yb2O3 and La2O3 is prepared in the mass ratio of 83%, 3%, 6%, 4%, 3.5% and 0.5%.

[0033] Embodiment 4: The SiAlON ceramic of this embodiment can be used to make heat-resistant metal cutting tools for intermittent cutting. Its crystal phase structure includes α-SiAlON phase and β-SiAlON phase. The proportion of α-SiAlON phase is about 39%, and the proportion of β-SiAlON phase is about 61%. The SiAlON ceramic also includes three rare earth elements: Y, Yb and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.0% of the theoretical density, a hardness of HV10 of 1760, and a fracture toughness of K 1C 8.5 MPa / m 2 The microscopic morphology of SiAlON ceramics (SEM image) is as follows: Figure 6 As shown by Figure 6 It can be seen that the microstructure is dense and an obvious long rod-shaped β-SiAlON structure can be observed. The X-ray diffraction pattern of SiAlON ceramics in the range of 29.5°-38.5° is as follows Figure 7 shown.

[0034] The preparation method of the SiAlON ceramic of this embodiment comprises the following steps: (1) Combine Si3N4, Al2O3, AlN, Y2O 3、Yb2O3 and La2O3 were prepared in a mixed powder at a mass ratio of 83%, 3%, 6%, 4%, 3.5% and 0.5%. Grinding balls and solvents were prepared in a ratio of mixed powder: Si3N4 balls: anhydrous ethanol = 1:2:3. In addition, 4% of the weight of the powder was added to the slurry as a binder, and the mixture was ball-milled at a speed of 250 rpm in a planetary ball mill for 8 hours to obtain a mixed slurry.

[0035] (2) The mixed slurry is vacuum dried and passed through an 80-mesh screen to obtain a mixed powder. The mixed powder is then placed in a mold for uniaxial pressing and then subjected to cold isostatic pressing at 200 MPa to obtain a ceramic green body.

[0036] (3) After the ceramic green body is placed in a resistance furnace to remove the binder (800°C, 3h), it is transferred to a pressure sintering furnace. First, the temperature is raised to 1500°C at a rate of 10°C / min under vacuum, and then raised to 1800°C at a rate of 8°C / min under 0.1 MPa nitrogen protection. At this sintering temperature, 1 MPa N2 is applied to maintain the pressure for 1 hour, and then 8 MPa N2 is applied to maintain the pressure for 1 hour, and then cooled in the furnace to obtain SiAlON ceramics.

[0037] Embodiment 5: The SiAlON ceramic of this embodiment can be used to make heat-resistant metal cutting tools for intermittent cutting. Its crystal phase structure includes α-SiAlON phase and β-SiAlON phase, with the α-SiAlON phase accounting for about 34% and the β-SiAlON phase accounting for about 66%. The SiAlON ceramic also includes three rare earth elements: Y, Yb and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.1% of the theoretical density, a hardness of HV10 of 1740, and a fracture toughness of K 1C 8.5 MPa / m 2 .

[0038] The preparation method of the SiAlON ceramic of this embodiment comprises the following steps: (1) Combine Si3N4, Al2O3, AlN, Y2O 3、 Yb2O3 and La2O3 were prepared in a mixed powder at a mass ratio of 80.5%, 4%, 7%, 1%, 6% and 1.5%. Grinding balls and solvents were prepared in a ratio of mixed powder: Si3N4 balls: anhydrous ethanol = 1:2:3. In addition, 4% of the weight of the powder was added to the slurry as a binder, and the mixture was ball-milled at a speed of 250 rpm in a planetary ball mill for 8 hours to obtain a mixed slurry.

[0039] (2) The mixed slurry is vacuum dried and passed through an 80-mesh screen to obtain a mixed powder. The mixed powder is then placed in a mold for uniaxial pressing and then subjected to cold isostatic pressing at 200 MPa to obtain a ceramic green body.

[0040] (3) After the ceramic green body is placed in a resistance furnace to remove the binder (800°C, 3h), it is transferred to a pressure sintering furnace. First, the temperature is raised to 1500°C at a rate of 10°C / min under vacuum, and then raised to 1800°C at a rate of 8°C / min under 0.1 MPa nitrogen protection. At this sintering temperature, 1 MPa N2 is applied to maintain the pressure for 1 hour, and then 8 MPa N2 is applied to maintain the pressure for 1.5 hours, and then cooled in the furnace to obtain SiAlON ceramics.

[0041] Embodiment 6: The SiAlON ceramic of this embodiment can be used to make heat-resistant metal cutting tools for intermittent cutting. Its crystal phase structure includes α-SiAlON phase and β-SiAlON phase. The proportion of α-SiAlON phase is about 36%, and the proportion of β-SiAlON phase is about 64%. The SiAlON ceramic also includes three rare earth elements: Y, Yb and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.0% of the theoretical density, a hardness of HV10 of 1750, and a fracture toughness of K 1C 8.1 MPa / m 2 .

[0042] The preparation method of the SiAlON ceramic of this embodiment comprises the following steps: (1) Combine Si3N4, Al2O3, AlN, Y2O 3、 Yb2O3 and La2O3 were prepared in a mixed powder at a mass ratio of 83.5%, 1.5%, 3.5%, 2%, 7.5% and 2%. Grinding balls and solvents were prepared in a ratio of mixed powder: Si3N4 balls: anhydrous ethanol = 1:2:3. In addition, 4% of the weight of the powder was added to the slurry as a binder, and the mixture was ball-milled at a speed of 250 rpm in a planetary ball mill for 8 hours to obtain a mixed slurry.

[0043] (2) The mixed slurry is vacuum dried and passed through an 80-mesh screen to obtain a mixed powder. The mixed powder is then placed in a mold for uniaxial pressing and then subjected to cold isostatic pressing at 200 MPa to obtain a ceramic green body.

[0044] (3) After the ceramic green body is placed in a resistance furnace to remove the binder (800°C, 3h), it is transferred to a pressure sintering furnace. First, the temperature is raised to 1500°C at a rate of 10°C / min under vacuum, and then raised to 1800°C at a rate of 8°C / min under 0.1 MPa nitrogen protection. At this sintering temperature, 1 MPa N2 is applied to maintain the pressure for 1 hour, and then 10 MPa N2 is applied to maintain the pressure for 1.5 hours, and then cooled in the furnace to obtain SiAlON ceramics.

[0045] Embodiment 7: The SiAlON ceramic of this embodiment can be used to make heat-resistant metal cutting tools for intermittent cutting. Its crystal structure includes α-SiAlON phase and β-SiAlON phase, with the α-SiAlON phase accounting for about 35% and the β-SiAlON phase accounting for about 65%. The SiAlON ceramic also includes three rare earth elements: Y, Yb and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.3% of the theoretical density, a hardness of HV10 of 1720, and a fracture toughness of K 1C 8.3 MPa / m 2 .

[0046] The preparation method of SiAlON ceramics in this embodiment is basically the same as that in embodiment 6, the only difference is that in step (1) of this embodiment, Si3N4, Al2O3, AlN, Y2O 3、 The mixed powder of Yb2O3 and La2O3 is prepared in the mass ratio of 87%, 2.5%, 2%, 3%, 5% and 0.5%.

[0047] Embodiment 8: The SiAlON ceramic of this embodiment can be used to make heat-resistant metal cutting tools for intermittent cutting. Its crystal phase structure includes α-SiAlON phase and β-SiAlON phase. The proportion of α-SiAlON phase is about 31%, and the proportion of β-SiAlON phase is about 69%. The SiAlON ceramic also includes three rare earth elements: Y, Yb and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.1% of the theoretical density, a hardness of HV10 of 1700, and a fracture toughness of K 1C 8.2 MPa / m 2 .

[0048] The preparation method of the SiAlON ceramic of this embodiment comprises the following steps: (1) Combine Si3N4, Al2O3, AlN, Y2O 3、Yb2O3 and La2O3 were prepared in a mixed powder ratio of 85.5%, 2%, 2%, 2%, 7.5% and 1%. Grinding balls and solvents were prepared in a ratio of mixed powder: Si3N4 balls: anhydrous ethanol = 1:2:3. In addition, 4% of the weight of the powder was added to the slurry as a binder, and the mixture was ball-milled in a planetary ball mill at a speed of 250 rpm for 8 hours to obtain a mixed slurry.

[0049] (2) The mixed slurry is vacuum dried and passed through an 80-mesh screen to obtain a mixed powder. The mixed powder is then placed in a mold for uniaxial pressing and then subjected to cold isostatic pressing at 200 MPa to obtain a ceramic green body.

[0050] (3) After the ceramic green body is placed in a resistance furnace to remove the binder (800°C, 3h), it is transferred to a pressure sintering furnace. First, the temperature is raised to 1500°C at a rate of 10°C / min under vacuum, and then raised to 1750°C at a rate of 8°C / min under 0.1 MPa nitrogen protection. At this sintering temperature, 1 MPa N2 is applied to maintain the pressure for 1 hour, and then 10 MPa N2 is applied to maintain the pressure for 1.5 hours, and then cooled in the furnace to obtain SiAlON ceramics.

[0051] Embodiment 9: The SiAlON ceramic of this embodiment can be used to make wear-resistant parts or heat-resistant metal cutting tools for continuous cutting. Its crystal phase structure includes α-SiAlON phase and β-SiAlON phase, with the proportion of α-SiAlON phase being about 53% and the proportion of β-SiAlON phase being about 47%. The SiAlON ceramic also includes three rare earth elements: Y, Er and La. The SiAlON ceramic of this embodiment has been tested to have a relative density of 99.0% of the theoretical density, a hardness of HV10 of 1820, and a fracture toughness of K 1C 8.0 MPa / m 2 .

[0052] The preparation method of the SiAlON ceramic of this embodiment is basically the same as that of Example 1, with the only difference being that in step (1) of this embodiment, Si3N4, Al2O3, AlN, Y2O3, Er2O3 and La2O3 are mixed in a powder ratio of 82%, 3%, 6%, 1.7%, 6.1% and 1.2%.

[0053] Comparative Example 1: The preparation method of the SiAlON ceramic of this comparative example is basically the same as that of Example 1, except that in step (1) of this comparative example, Si3N4, Al2O3, AlN, Y2O 3、The mixed powder of Yb2O3 and La2O3 is prepared in the mass ratio of 81%, 2.8%, 5.7%, 1.5%, 5.7% and 3.3%.

[0054] The SiAlON ceramics prepared in this comparative example have a relative density of 99.0%, a hardness HV10 of 1650, and a fracture toughness K 1C 6.8 MPa / m 2 Its microstructure has no obvious pores, but the ratio of intercrystalline glass phase is high and there is slight glass phase aggregation in some areas (such as Figure 8 As shown in the dotted box, its hardness and fracture toughness are low, and the aggregated grain boundary glass phase may become the source of high-temperature creep. The proportion of α-SiAlON is about 52%, and the proportion of β-SiAlON is about 48%.

[0055] Comparative Example 2: The preparation method of the SiAlON ceramic in this comparative example is basically the same as that in Example 5, with the only difference being that in step (1) of this comparative example, Si3N4, Al2O3, AlN, Y2O3 and La2O3 are mixed in powder according to a mass ratio of 80.5%, 4%, 7%, 7% and 1.5%.

[0056] The SiAlON ceramics prepared in this comparative example have Y and RE III The rare earth cations are too large to be the coordinating cations of α-SiAlON. The proportion of α-SiAlON is about 22%, and the proportion of β-SiAlON is about 78%. The relative density is 98.8%, the hardness HV10 is 1650, and the fracture toughness K 1C 7.5 MPa / m 2 In comparison, its wear resistance is poor, which may affect its service life.

[0057] Comparative Example 3: The preparation method of the SiAlON ceramic of this comparative example comprises the following steps: (1) Combine Si3N4, Al2O3, AlN, Y2O 3、 Yb2O3 and La2O3 were prepared in a mixed powder at a mass ratio of 83%, 3%, 6%, 4%, 3.5% and 0.5%. Grinding balls and solvents were prepared in a ratio of mixed powder: Si3N4 balls: anhydrous ethanol = 1:2:3. In addition, 4% of the weight of the powder was added to the slurry as a binder, and the mixture was ball-milled at a speed of 250 rpm in a planetary ball mill for 8 hours to obtain a mixed slurry.

[0058] (2) The mixed slurry is vacuum dried and passed through an 80-mesh screen to obtain a mixed powder. The mixed powder is then placed in a mold for uniaxial pressing and then subjected to cold isostatic pressing at 200 MPa to obtain a ceramic green body.

[0059] (3) After the ceramic green body is placed in a resistance furnace to remove the binder (800°C, 3h), it is transferred to a pressure sintering furnace. First, the temperature is raised to 1500°C at a rate of 10°C / min under vacuum, and then the temperature is raised to 1800°C at a rate of 8°C / min under 0.1 MPa nitrogen protection. At this sintering temperature, 1 MPa N2 is applied for 2.5 hours of pressure maintenance, and then the SiAlON ceramic is obtained by cooling in the furnace.

[0060] The SiAlON ceramic prepared in this comparative example is not effective in eliminating the closed pores in the later stage because high pressure sintering is not used in the later stage of sintering. After testing, its relative density is 97.9%, and there are a small number of micropores in the microstructure. Its hardness HV10 is 1600, and its fracture toughness K 1C 7.2 MPa / m 2 In comparison, its wear resistance is poor, which may affect its service life. The proportion of α-SiAlON in the comparative example is about 38%, and the proportion of β-SiAlON is about 62%.

[0061] Comparative Example 4: The preparation method of the SiAlON ceramic of this comparative example comprises the following steps: (1) Combine Si3N4, Al2O3, AlN, Y2O 3、 Yb2O3 and La2O3 were prepared in a mixed powder at a mass ratio of 83%, 3%, 6%, 4%, 3.5% and 0.5%. Grinding balls and solvents were prepared in a ratio of mixed powder: Si3N4 balls: anhydrous ethanol = 1:2:3. In addition, 4% of the weight of the powder was added to the slurry as a binder, and the mixture was ball-milled at a speed of 250 rpm in a planetary ball mill for 8 hours to obtain a mixed slurry.

[0062] (2) The mixed slurry is vacuum dried and passed through an 80-mesh screen to obtain a mixed powder. The mixed powder is then placed in a mold for uniaxial pressing and then subjected to cold isostatic pressing at 200 MPa to obtain a ceramic green body.

[0063] (3) After the ceramic green body is placed in a resistance furnace to remove the binder (800°C, 3h), it is transferred to a pressure sintering furnace. First, the temperature is raised to 1500°C at a rate of 10°C / min under vacuum, and then the temperature is raised to 1650°C at a rate of 8°C / min under 0.1 MPa nitrogen protection. At this sintering temperature, 1 MPa N2 is applied to maintain the pressure for 1 hour, and then 8 MPa N2 is applied to maintain the pressure for 1 hour, and then the SiAlON ceramic is obtained by cooling in the furnace.

[0064] The SiAlON ceramic prepared in this comparative example has a high porosity due to the low sintering temperature. After testing, its relative density is 96.5%, and there are a small number of micropores in the microstructure (such as Fig. 9 Its hardness HV10 is 1510 and its fracture toughness K 1C 6.2MPa / m 2 In comparison, its wear resistance is poor, which may affect its service life. The proportion of α-SiAlON in the comparative example is about 21%, and the proportion of β-SiAlON is about 79%.

[0065] The components, final sintering temperature, pressure of the second stage at the final sintering temperature and holding time in each embodiment and comparative example are shown in Table 1; the relative density, hardness HV10, fracture toughness K 1C The α phase ratio (i.e., α% / (α%+β%)) is shown in Table 2.

[0066] Table 1: Comparison of ceramic components and preparation processes of various embodiments and comparative examples

[0067] Table 2: Test results of ceramic properties of various embodiments and comparative examples

[0068] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

[0069] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A SiAlON ceramic, characterized in that: The crystal phase structure of the SiAlON ceramic includes an α-SiAlON phase and a β-SiAlON phase; the SiAlON ceramic also includes three rare earth elements: Y, RE II and RE III ; The rare earth element RE II The cation radius is less than 0.89Å; the rare earth element RE III The cation radius is larger than 1.0 Å.

2. The SiAlON ceramic according to claim 1, characterized in that: The rare earth element RE II Includes at least one of Lu, Yb, Tm and Er.

3. The SiAlON ceramic according to claim 1, characterized in that: The rare earth element RE III Includes at least one of Ce and La.

4. The SiAlON ceramic according to any one of claims 1 to 3, characterized in that: In the SiAlON ceramic, the proportion of the α-SiAlON phase is 25% to 70%, and the proportion of the β-SiAlON phase is 30% to 75%.

5. A method for preparing the SiAlON ceramic according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Combine Si3N4, AlN, Al2O3, Y2O3, RE II2 O3 and RE III2 The O3 raw material powder and the binder are dispersed in a solvent according to a proportion and mixed evenly to obtain a mixed slurry; (2) drying the mixed slurry and then performing molding to obtain a ceramic green body; (3) The ceramic green body is sintered under pressure at 1700-1900° C., and then cooled after sintering to obtain the SiAlON ceramic.

6. The method for preparing SiAlON ceramics according to claim 5, characterized in that: In step (3), the ceramic green body is first heated to 1500° C. under vacuum conditions, then heated to 1700-1900° C. at a rate of 5-8° C. / min in a nitrogen atmosphere of 0.1 MPa, and pressure sintered in a nitrogen atmosphere of 1-10 MPa.

7. The method for preparing SiAlON ceramics according to claim 6, characterized in that: After the ceramic green body is heated to 1700-1900° C., two-step pressure sintering is performed: first, it is kept warm for 1 hour in a nitrogen atmosphere at 1 MPa, and then it is kept warm for 1-1.5 hours in a nitrogen atmosphere at 6-10 MPa.

8. The method for preparing SiAlON ceramics according to any one of claims 5 to 7, characterized in that: Si3N4 powder accounts for 75~90wt% of the total mass of raw material powder; AlN powder accounts for 2~8wt% of the total mass of raw material powder; Al2O3 powder accounts for 1~5wt% of the total mass of raw material powder; Y2O3 powder accounts for 0~10wt% of the total mass of raw material powder; RE II2 O3 powder accounts for 1~11wt% of the total mass of raw material powder; RE III2 O3 powder accounts for 0.1~2wt% of the total mass of raw material powder; among them, Y2O3+RE II2 O3+RE III2 The sum of O3 powder accounts for 5~12wt% of the total mass of raw material powder.

9. The method for preparing SiAlON ceramics according to any one of claims 5 to 7, characterized in that: The binder includes at least one of polyvinyl butyral and microcrystalline wax; the added amount of the binder is 1-6% of the total mass of the raw material powder.

10. Use of the SiAlON ceramic according to any one of claims 1 to 4 or the SiAlON ceramic prepared by the preparation method according to any one of claims 5 to 9, characterized in that: The SiAlON ceramic is used for making heat-resistant metal high-speed machining tools, wear-resistant components or high-temperature refractory materials.

Citation Information

Patent Citations

  • SiAION containing ytterbium and method of making

    CN1246254C